STRATEGI GURU PPKn DALAM MENGEMBANGKAN KARAKTER DISIPLIN SISWA KELAS VlI DI SMPN 3 WOJA - YULIASTINA, YULIASTINA; ISMAIL, M.; ALHADIKA, MUHAMMAD; ZUBAIR, MUHAMMAD (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This research is motivated by the existence of PPKn teacher strategies in developing the disciplined character of class Vll students at SMPN 3 Woja, where at SMPN 3 Woja this teacher strategy is really needed in developing this disciplinary character, especially PPKn teachers because PPKn teachers are one of the appropriate tools. In implementing the values ??of character education for students, basically the aim of PPKn is to make students become democratic citizens with character according to the values ??of Pancasila. When talking about PPKn subject teachers, it is carried out in character education co-curricular activities which are implemented in all subjects including PPKn subject matter. Discipline is very important to apply to students, discipline should not only enforce long-term rules, but also be able to raise high levels of students. The process of developing disciplined character can have a positive impact on students' emotional, spiritual and personality development. This is done in a simple way, being disciplined in coming to school on time, wearing a uniform according to the applicable rules, being disciplined in carrying out routine school activities. The researcher's goal is to find out. To describe the strategies faced by teachers in developing students' disciplined character and to describe the factors that influence teachers' strategies in developing the disciplined character of class Vll students at SMPN 3 Woja. This research uses qualitative research with a descriptive research type. The subject of this research is Civics Teachers. The informants from this research are the Principal, Deputy Head of Student Affairs, Guidance and Guidance Teachers, students, SMPN 3 Woja and the data collection techniques in this research can be concluded that at SMPN 3 Woja the PPKn teacher's strategy to develop students' Disciplinary Character has been implemented well, as in developing the teacher's character by applying strategies starting from time discipline, attitude discipline and rule discipline. ABSTRAKPenelitian ini di latar belakangi dengan adanya strategi guru PPKn dalam mengembangakan karakter disiplin siswa kelas Vll di SMPN 3 Woja yang dimana di SMPN 3 Woja ini strategi guru sangat dibutuhkan dalam mengembangkan karakter disiplin tersebut terutama guru PPKn dikarenakan Guru mapel PPKn sebagai salah satu sarana yang tepat dalam implementasikan nilai-nilai pendidikan karakter peserta didik pada dasarnya tujuan PPKn adalah untuk menciptakan peserta didik menjadi warga negara yang demokrasu dan berkarakter sesuai nilai-nilai Pancasila. Ketika berbicara guru mapel PPKn dilakukan dalam kegiatan Korikuler pendidikan karakter diwujudkan semua mata pelajaran termaksuk mapel PPKn. Disiplin sangat penting untuk diterapkan bagi siswa, disiplin seharusnya tidak hanya menegakkan aturan jangka Panjang, tetapi juga mampu meningkatkan peserta didik yang tinggi. Proses pengembangan karakter disiplin dapat memberikan dampak positif bagi perkembangan emosional, spiritual dan kepribadian siswa. Untuk mendiskripsikan Strategi yang dihadapi Guru dalam mengembangkan karakter disiplin siswa serta mendiskripsikan faktor yang mempengaruhi strategi guru dalam mengembangkan karakter disiplin siswa kelas Vll di SMPN 3 Woja. Penelitian ini menggunakan penelitian kualitatif dengan jenis penelitian Diskriptif adapun subjek dari penelitian ini yaitu Guru PPKn. Informan dari penelitian ini yaitu Kepala Sekolah, Wakasek Kesiswaan, Guru BK, Siswa-siswi, SMPN 3 Woja dan teknik pengumpulan data dalam penelitian inidapat dsimpulkan bahwa di SMPN 3 Woja strategi guru PPKn dalam mengembangkan Karakter Disiplin siswa sudah dijalankan dengan baik yang diman dalam mengembangkan karakter tersebut guru memberlakukan strateginya mulai dari disiplin waktu, disiplin waktu, disiplin sikap dan disiplin aturan.